Solusi Kepemimpinan Pendidikan di Tengah Tantangan Ekonomi Global: Fokus pada Pengembangan Sumber Daya Manusia" - Ahmad Fatkhul Labibur Rohman (SETYAKI : Jurnal Studi Keagamaan Islam, 2025)
This research aims to analyze and formulate effective educational leadership solutions in facing global economic challenges, emphasizing the development of human resources (HR) as a key success factor. Amid the economic uncertainty impacting the education sector, adaptive and transformational leadership becomes crucial in managing change and ensuring the quality of learning is maintained. The research method used is a descriptive qualitative approach with data collection techniques through in-depth interviews, documentation studies, and observations of leadership practices at Mts Al Huda Tulungagung. The results of the study show that leadership oriented towards collaboration, strengthening the capacity of teachers and educational staff, and the strategic utilization of technology can enhance the resilience and competitiveness of educational institutions amidst global pressures. In addition, the commitment to human resource development has proven to play a central role in creating innovation and efficiency in education management. The contribution of this research lies in providing a conceptual framework and strategic recommendations for policymakers and education practitioners in formulating a leadership model that is responsive to global dynamics and sustainable in nurturing superior human resources.